Pengaruh Disiplin Kerja, Stres Kerja dan Beban Kerja Kerja Terhadap Kinerja Karyawan Logistik PT. Permata Hijau Palm Oleo KIM II - Azwan, Chairil; Lubis, Kartika Sari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Performance improvement is a fundamental aspect in company management to achieve organizational goals, maintain survival, and maintain existence in the midst of increasingly competitive business competition. This study aims to analyze the effect of work discipline, work stress, and workload on employee performance at PT Permata Hijau Palm Oleo KIM II. The research method used is quantitative descriptive research using primary and secondary data obtained directly from related companies. Data analysis techniques include multiple linear regression statistical tests to measure the relationship between independent variables (work discipline, work stress, and workload) on the dependent variable (employee performance). The results showed that work discipline has no significant effect on employee performance, with a tcount value of 0.452 smaller than the ttable 1.984 (0.452 < 1.984) and a significance value of 0.653 which is greater than 0.05 (0.653 > 0.05). Conversely, work stress has a positive and significant effect on employee performance, as evidenced by the tcount value of 5.584 which is greater than the ttable 1.984 (5.584 > 1.984) and a significance value of 0.000 which is less than 0.05 (0.000 < 0.05). In addition, workload also has a positive and significant effect on employee performance with a tcount value of 2.317 which is greater than the t table 1.984 (2.317 > 1.984) and a significance value of 0.023 which is smaller than 0.05 (0.023 < 0.05). Based on these findings, it can be concluded that work stress and workload have a significant influence on improving employee performance, while work discipline does not have a significant impact. The implication of this study indicates the need for the management of PT Permata Hijau Palm Oleo KIM II to pay attention to stress and workload factors in order to increase the productivity and effectiveness of employee performance.